1991
DOI: 10.1002/ajmg.1320390218
|View full text |Cite
|
Sign up to set email alerts
|

Dandy–Walker malformation in the Meckel syndrome

Abstract: The Meckel syndrome is an autosomal recessive condition and includes a heterogeneous group of CNS malformations, most frequently occipital encephalocele. We report on 2 sibs and one other unrelated case with Meckel syndrome in whom the CNS anomaly was the Dandy-Walker malformation, an association not previously described. The criteria used to diagnose the Meckel syndrome are also reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…Cases 4 and 5 in our series are similar to the postnatal description by Kudo et al [3], and the prenatal diagnosis made later by other authors [2,14]. Both cases are the first diagnosed by first trimester ultrasound examination.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Cases 4 and 5 in our series are similar to the postnatal description by Kudo et al [3], and the prenatal diagnosis made later by other authors [2,14]. Both cases are the first diagnosed by first trimester ultrasound examination.…”
Section: Discussionsupporting
confidence: 76%
“…We compare our cases and their prognosis to the ones in the literature. Two of our cases are siblings from consanguineous parents where the Dandy-Walker malformation is part of a variant of Meckel syndrome already described in the literature [2][3][4]. These 2 cases are the first described in the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Other malformations may be observed in MKS, for example cleft palate with or without cleft lip, microphthalmia, cystic and fibrotic changes of other visceral organs such as pancreas and epididymis (Rehder and Labbé 1981;Seller 1981;Rapola and Salonen 1985) and congenital heart defect. Cases with DandyWalker malformation, with or without polydactyly, have also been reported (Goldston et al 1963;Kudo et al 1985;Herriot et al 1991;Walpole et al 1991;Moerman et al 1993;Summers and Donnenfeld 1995;Al-Gazali et al 1996). Whether Dandy-Walker malformation is part of the true MKS or whether these cases represent atypical MKS is controversial.…”
Section: Introductionmentioning
confidence: 87%
“…Ahdab-Barmada and Claassen [22] suggested that a distinctive triad of CNS malformations (prosencephalic dysgenesis, occipital encephalocele, and rhombic roof dysgenesis) should be included in the diagnostic criteria of MKS. Herriot et al [23] suggested that the DandyWalker malformation (DWM) should be accepted as one of the malformations associated with MKS. It had been debated that DWM coexisting with typical features of MKS should, perhaps, be treated as a different recessive syndrome.…”
Section: Clinical Features Of Meckel-gruber Syndromementioning
confidence: 99%